Optimizing Maternal Health Outcomes: Examining the Relationship Between Primary Healthcare Center Organizational Characteristics and Maternal and Child Health (MCH) Handbook Utilization in Counseling - Barirah Madeni; Hasritawati (HM Publisher, 2025)
Maternal mortality remains a significant global health challenge, disproportionately affecting low- and middle-income countries. The Maternal and Child Health (MCH) Handbook is a valuable tool for providing essential health information and promoting timely care-seeking behaviors during pregnancy. This study investigates the influence of primary healthcare center (PHC) organizational characteristics on the utilization of MCH Handbooks as counseling materials for pregnant women in Aceh Tengah District, Indonesia. A cross-sectional survey was conducted among 208 midwives across 17 PHCs in Aceh Tengah District. Data were collected on organizational characteristics (organizational climate, supervision, and leadership) and the utilization of MCH Handbooks in antenatal counseling sessions. Descriptive statistics, Chi-square tests, and logistic regression were used to analyze the data. The study found that 68.3% of midwives reported inadequate utilization of MCH Handbooks in counseling sessions. Supervision (p=0.006) and leadership (p=0.000) were significantly associated with MCH Handbook utilization, while organizational climate (p=0.738) showed no significant association. In conclusion, PHC organizational characteristics, particularly supervision and leadership, play a crucial role in promoting the effective use of MCH Handbooks in antenatal counseling. Strengthening supervision and leadership support within PHCs can enhance MCH Handbook utilization and potentially contribute to improved maternal health outcomes.